Description of empathetic listening of school counselors on the counseling among problematic students - Fitri, Susi; Mamesah, Michiko; Safitri, Dita Amalia (Konselor, 2019)
This study aims to describeÂ empathetic listening to school counselors and directing students to difficulties. The samples in this study were 106 school counselors. Sampling method used proportional random sampling technique. The research method used is a descriptive survey. Data collection uses the School Empathy Counselor Inventory which comprises 42 items approved with reliability test results got 0.9405. The results of the study showed that most empathy listened to school counselors in students having problems with moderate categories. School Counselors are capable when listening to problem students. However, for school counselors aged 41-50 years, there was a decrease in empathy and teachers of empathy for women higher than men, so counseling training was needed to increase empathy and listening skills.